Analisis Pengaruh Dana Pihak Ketiga dan Pembiayaan Terhadap Market Share Perbankan Syariah di Indonesia Melalui Aset Sebagai Variabel Intervening - Vivin Wulandari; Deky Anwar (LPMP Imperium, 2019)
Purpose- This study aims to analyze the direct and indirect effect of Third Party Funds (TPF) and Financing (PMBY) on the Market share (MS) of Indonesian Islamic Banking in 2013-2017, with asset variables (ASET) as intervening. Methods- A quantitative research method was used. Data collection techniques in this study are documentation financial reporting. Panel data regression is used to test hypotheses using the EVIEWS program Findings- The results indicate that simultaneous, TPF, PMBY, and ASET have a positive and significant effect on the market share of Islamic banking. And partially, TPF does not affect MS, PMBY has a significant negative effect on MS, and assets have a significant positive effect on MS. ASET are not proven to be intervening on the tested model. Research implications- This study can be a knowledge for investors to understand the market share of Islamic banking, as well as an evaluation material for management to increase market share through deposits, PMBY, and ASET.